Corrosion-fatigue life of commercially pure titanium and Ti-6Al-4V alloys in different storage environments - Zavanelli, R. A.; Henriques, GEP; Ferreira, I; Rollo, JMDD (Mosby, Inc, 2000)
Statement of problem. Removable partial dentures are affected by fatigue because of the cyclic mechanism of the masticatory system ansi frequent insertion and removal. Titanium and its alloys have been used in the manufacture of denture frameworks; however, preventive agents with fluorides are thought to attack titanium alloy surfaces.Purpose. This study evaluated, compared, analyzed the corrosion-fatigue life of commercially pure titanium and Ti-6Al-4V alloy in different storage environments.Material and methods. For each metal, 33 dumbbell rods, 2.3 mm in diameter at the central segment, were cast in the Rematitan system. Corrosion-fatigue strength test was carried out through a universal testing machine with a load 30% lon er than the 0.2% offset yield strength and a combined influence of different: environments: in air at room temperature, with synthetic saliva, and with fluoride synthetic saliva. After failure, the number of cycles were recorded, and fracture surfaces were examined with on SEM.Results. ANOVA and Tukey's multiple comparison rest indicated that Ti-6Al-4V alloy achieved 21,269 cycles (SD = 8,355) against 19,157 cycles (SD = 3,624) for the commercially purr Ti. There were no significant differences between either metal in the corrosion-fatigue life for dry specimens, but when the solutions were present, the fatigue life was significantly reduced, probably because of the product-ion of corrosion pits caused by superficial reactions.